Peranan Komunitas Harapan dalam Meningkatkan Kemandirian Anak Usia Sekolah di Kawasan Pasar Johar Semarang - Hasanah, Nur; Raharjo, Tri Joko; Yusuf, Amin (Journal of Nonformal Education and Community Empowerment, 2017)
The Komunitas Harapan has a role in shaping the child's independence. This study aims to describe the role of community expectations and constraints in improving the independence of school-aged children in Pasar Johar Market Semarang. This study used a qualitative descriptive approach with the subject of research consisting of the targeted community supporters, initiators of community expectations, managers, and citizens. Data collection techniques through observation, interview, and documentation. The validity of data using triangulation of sources, methods, and theories. Data analysis using interactive model. The result of the research shows that role of the Komunitas Harapan in improving the independence of school-aged children includes facilitative role, educative role, and representative role. The obstacles are the limited coordination between the Komunitas Harapan organizer and the parents of the assisted children.